Clinical outcomes and characteristics of critically ill patients with influenza- and COVID-19-induced ARDS: A retrospective, matched cohort study - Volkov, Lev; Delpuech, Marion; Conrad, Marie; Courte, Guilhem; Cravoisy, Aurélie; Nace, Lionel; Baumann, Cedric; Gibot, Sébastien (Frontiers in Medicine, 2023)
Seasonal epidemic influenza and SARS-CoV-2 are the most frequent viruses causing acute respiratory distress syndrome (ARDS). To what extent these two etiologies differ in ICU patients remains uncertain. We therefore aimed at comparing the severity and outcomes of influenza and SARS-CoV-2 induced ARDS in mechanically ventilated patients. This retrospective, analytic, single-center study was conducted in the medical ICU of Nancy University Hospital in France. Adult patients hospitalized with confirmed influenza (from 2009 to 2019) or SARS-CoV-2 (between March 2020 and May 2021) induced ARDS and under mechanical ventilation were included. Each influenza patient was matched with two COVID-19 patients, with the same severity of ARDS. The primary endpoint was death in ICU on day 28. The secondary endpoints were the duration of vasopressors, the use of renal-replacement therapy, the duration of mechanical ventilation, and the ICU length of stay. Forty-two influenza patients were matched with 84 COVID-19 patients. They had similar sex distribution, age, Charlson Comorbidity index, and ARDS severity. At day 28, 11 (26.2%) patients in the influenza group, and 9 (10.7%) in the COVID-19 group had died (p=0.0084, HR= 3.31, CI 95% [1.36-8.06]). In univariate cox model, being infected with SARS-CoV-2, SOFA and SAPS II scores, initial arterial pH, PaCO2, PaO2/FiO2, serum lactate level, platelets count, and use of renal replacement therapy were significantly associated with mortality. In multivariate Cox model, the SOFA score at admission (p<0.01, HR=1.284, CI 95% [1.081;1.525]), and the initial pH (p<0.01, HR=0.618, CI 95% [0.461; 0.828]) were the only predictors of mortality. The kind of virus had no influence on mortality, although COVID-19 patients underwent longer mechanical ventilation, and received more neuro-muscular blockers and prone positioning. In mechanically ventilated ARDS patients, 28-day mortality was higher among influenza patients as compared to COVID-19, because of a higher initial extra-pulmonary severity. However, the kind of virus was not, by itself, correlated with mortality.